History of the development of telecommunications infrastructure in Japan - Yoshio Arai (Netcom)
Japan has one of the most well-equipped telecommunications infrastructures in the world. The rich Japanese information environment is the result of a long telecommunications infrastructure construction process. This paper describes the historical process of the development of Japan’s telecommunications infrastructure from the introduction of telegraph technology in the late 19th century to the recent expansion of mobile broadband. From the early stage of the construction of telegraph networks, an efficient geographical configuration for Japan’s international telecommunications has been sought. First, a westward route to European countries was built at the beginning of telegraph services and then the eastward route connected directly to the United States was opened. During the construction of the international coaxial submarine cables after World War II, the combined use of the westward and eastward telecommunications routes similar to the early international telegraph networks was retained. In the early 2000s, ultra-high-speed trans-Pacific telecommunications networks were constructed corresponding to rapid expansion of Internet use. The main route of Japan’s international communications shifted to the eastward one. In contrast, the geographical configuration of the domestic telecommunications in Japan has been essentially unchanged. The domestic telegraph networks had been steadily expanded from the large metropolises to local cities from the end of the 19th century to the early 20th century. Even the recent optical fiber networks maintain a similar configuration. Although new broadband services, e.g., DSL, optical fiber and mobile telecommunications, were installed corresponding to the expansion of Internet use, the geographical configuration of domestic telecommunications networks has been kept.